Thermal fluctuations assist mechanical signal propagation in coiled-coil proteins - Clopes, Judit; Shin, Jaeoh; Jahnel, Marcus; Grill, Stephan W.; Zaburdaev, Vasily (Physical Review E, 2021)
Recently, it has been shown that the long coiled-coil membrane tether protein early endosome antigen 1 (EEA1) switches from a rigid to a flexible conformation upon binding of a signaling protein to its free end. This flexibility switch represents a motorlike activity, allowing EEA1 to generate a force that moves vesicles closer to the membrane they will fuse with. It was hypothesized that the binding-induced signal could propagate along the coiled coil and lead to conformational changes through the localized domains of the protein chain that deviate from a perfect coiled-coil structure. To elucidate, if upon binding of a single protein the corresponding mechanical signal could propagate through the whole 200-nm-long chain, we propose a simplified description of the coiled coil as a one-dimensional Frenkel-Kontorova chain. Using numerical simulations, we find that an initial perturbation of the chain can propagate along its whole length in the presence of thermal fluctuations. This may enable the change of the configuration of the entire molecule and thereby affect its stiffness. Our work sheds light on intramolecular communication and force generation in long coiled-coil protein
Keywords: Intracellular signalling; Signal transduction; Proteins